Surface electrocardiogram: Could atrioventricular nodal and His bundle potentials be recorded beat by beat on “Saah electrocardiogram”? - Chang, Qinghua (Anatol J Cardiol, 2017)
OBJECTIVE: The P-QRS-T wave on surface electrocardiogram (ECG) reflects the changes in atrial and ventricular electrical properties. However, the atrioventricular conduction system potentials cannot be recorded to date. This study aimed to explore the possibility of micropotential of the atrioventricular conduction system recorded by surface “SAN-Atrial-AVN-His (Saah) ECG.” METHODS: We randomized 100 healthy volunteers (50 females and 50 males; mean age 25.12±1.62 years) to receive “conventional 12-lead ECG” and “Saah ECG,” which were recorded by the “Saah ECG” machine. We recorded and further analyzed “conventional 12-lead ECG” and “Saah ECG.” According to the microwavelets before the QRS complex, the PR interval was the sum of three intervals: PAs interval (PA interval recorded on surface ECG), AHs interval (AH interval recorded on surface ECG), and HVs interval (HV interval recorded on surface ECG). The PR interval, PAs interval, AHs interval, and HVs interval were measured. RESULTS: Not only the P-QRS-T waves but also the microwavelets before the P wave, before the QRS complex, and after the QRS complex were recorded in 100 healthy volunteers. The PAs interval, AHs interval, and HVs interval were 22–37 (31.23±2.93) ms, 60–103 (76.07±13.43) ms, and 39–55 (49.29±4.44) ms, respectively. The PAs interval, AHs interval, and HVs interval were consistent with the intracardiac measurements (PA, AH, and HV intervals) obtained in previous studies. Compared with female volunteers, male volunteers had a longer AHs interval (p<0.05). CONCLUSION: Not only the P-QRS-T waves but also the microwavelets before the P wave, before the QRS complex, and after the QRS complex were recorded on surface ECG. The wavelets before the QRS complex may be related to atrioventricular nodal, His bundle (bundle branch) potentials.